Integrated Planning of Heat Flows in Production Systems - Kurle, Denis (Sustainable Production, Life Cycle Engineering and Management, 2018)
The book presents an integrated planning concept for heat flows in production systems comprising various short term and long term related models. Detailed explanations about the modeling and implementation of all relevant system elements such as generic and specific machines types, technical building services (TBS), production planning and control aspects, heat storage units and (waste) heat designs follow. Due to resulting amounts of data, the concept foresees system level appropriate indicators and visualizations for a facilitated evaluation of the model results. An application procedure embeds and describes all models as well. Three exemplary application cases demonstrate the applicability, including the manufacturing of shafts for automotive transmissions, a cooling water system and an academic learning environment.